2015
DOI: 10.1371/journal.pone.0131365
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transposable Elements in the Origin and Evolution of MicroRNAs in Human

Abstract: MicroRNAs (miRNAs) are crucial regulators of gene expression at the post-transcriptional level in eukaryotes via targeting gene 3'-untranslated regions. Transposable elements (TEs) are considered as natural origins of some miRNAs. However, what miRNAs are and how these miRNAs originate and evolve from TEs remain unclear. We identified 409 TE-derived miRNAs (386 overlapped with TEs and 23 un-overlapped with TEs) which are derived from TEs in human. This indicates that the TEs play important roles in origin of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 35 publications
0
57
0
9
Order By: Relevance
“…In 2007, J. Piriyapongsa et al found that in humans TEs can be sources of microRNAs (Piriyapongsa et al, 2007), which was confirmed by other researchers (Yuan et al, 2010(Yuan et al, , 2011Qin et al, 2015). The key role of TEs in the formation of microRNAs and long ncRNAs (Johnson, Guigo, 2014;Kapusta, Feschotte, 2014) indicates that the maximum activity of TEs at the center of human neurogenesis (Kurnosov et al, 2015) as a natural phenomenon is necessary for epigenetic control of differentiation of neuronal stem cells.…”
Section: The Relationship Of Transposable Elements With Non-coding Rnmentioning
confidence: 83%
See 2 more Smart Citations
“…In 2007, J. Piriyapongsa et al found that in humans TEs can be sources of microRNAs (Piriyapongsa et al, 2007), which was confirmed by other researchers (Yuan et al, 2010(Yuan et al, , 2011Qin et al, 2015). The key role of TEs in the formation of microRNAs and long ncRNAs (Johnson, Guigo, 2014;Kapusta, Feschotte, 2014) indicates that the maximum activity of TEs at the center of human neurogenesis (Kurnosov et al, 2015) as a natural phenomenon is necessary for epigenetic control of differentiation of neuronal stem cells.…”
Section: The Relationship Of Transposable Elements With Non-coding Rnmentioning
confidence: 83%
“…Despite the lack of mitotic activity of mature neurons, the specific expression of TEs in them is important in controlling both interneuronal interactions and the structural and functional characteristics of neurons (Bailie et al, 2011;Richardson et al, 2014;Erwin et al, 2016). These properties may be due to processing from transcripts of transposons of specific long ncRNAs (Lu et al, 2014;Honson, Macfarlan, 2018) and microRNAs (Piriyapongsa et al, 2007;Yuan et al, 2010Yuan et al, , 2011Qin et al, 2015). Indeed, in experiments on laboratory animals, the enrichment of specific miRNAs in certain structures and regions of neurons was revealed.…”
Section: The Role Of Retroelements In Interactions Between Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). The palindromic nature of many transposons makes them plausible candidates for the evolutionary origin of miRNA genes (Piriyapongsa et al 2007;Roberts et al 2014;Qin et al 2015). For example, the placental-specific miR-1302 family was recently proposed to have originated from MER53 transposons (Yuan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…В ряде случаев этот процесс опосредован LTR-содержащими ретроэлементами (или эндогенными ретровирусами -HERV) и LINE (long interspersed nuclear elements) [43]. Большинство транспозонов (ТЕ -transposable element) в геноме человека расположены в межгенных областях, являясь важными источниками микроРНК [47][48][49] и функциональных доменов днРНК [50]. Количество копий L1 в гиппокампе (центр нейрогенеза человека) оказалось больше по сравнению с другими органами одного и того же человека [51].…”
Section: перспективы исследования транспозоновunclassified